Comparison between 6 weeks of static stretching and resistance training programs on passive and active properties of plantar flexors. a randomized controlled trial - Murakami, Yuta; Konrad, Andreas; Kasahara, Kazuki; Yoshida, Riku; Warneke, Konstantin; Behm, David G.; Nakamura, Masatoshi (Frontiers in Physiology, 2025)
IntroductionResistance training (RT) and static stretching (SS) are both exercises that increase range of motion (ROM), muscle strength, and muscle mass. This study aimed to compare the effects of SS and RT and examine factors related to the increase in ROM, muscle strength, and morphology.MethodsThirty-six healthy untrained male adults (age: 21.7 ± 1.2 years) were allocated to SS, RT, or control (no intervention) groups for a 6-week intervention program. Dorsiflexion (DF) ROM, passive torque at DF ROM, passive stiffness, maximal voluntary isometric contraction (MVC-ISO), MVC concentric (MVC-CON) and MVC eccentric (MVC-ECC) torques, and muscle thickness of plantar flexors were measured before and after the intervention.Results and discussionBoth SS and RT groups increased DF ROM (SS: p < 0.01, d = 0.65, RT: p = 0.038, d = 0.37) and passive torque at DF ROM (SS: p = 0.027, d = 0.64, RT: p < 0.01, d = 0.41) with similar small to moderate effect size magnitudes, while only the SS group experienced a significant, small magnitude decrease in passive stiffness (p = 0.025, d = −0.32). MVC-ISO, MVC-CON at 30°/s, and MVC-ECC torques at 30°/s showed small to large magnitude, significant increases in muscle strength (MVC-ISO at 30° plantarflexion: p < 0.01, d = 1.00, MVC-ISO at neutral position: p < 0.01, d = 0.43, MVC-ISO at 15° dorsiflexion: p < 0.01, d = 0.43, MVC-CON at 30°/s: p < 0.01, d = 0.38, MVC-ECC at 30°/s: p = 0.023, d = 0.48), whereas muscle thickness at medial and lateral gastrocnemius muscle (p < 0.001, d = 0.56 and p < 0.01, d = 0.66, respectively) exhibited significant, small magnitude increases only in the RT group. A significant positive correlation was found between the change in DF ROM and the change in passive torque at DF ROM in both SS (p < 0.001, r = 0.863) and RT (p < 0.001, rs = 0.825) groups, but no significant correlation was found between the change in DF ROM and passive stiffness. SS and RT increased ROM similarly, and both ROM increases may be due to changes in stretch tolerance. If increasing ROM and muscle strength is the goal, RT should be selected; conversely, if changes in ROM and passive stiffness are the goal, SS should be selected.